An ethical view on international trade agreements TTIP and CETA in the Republic of Croatia - Marinčić, Mile; Čović, Berislav (2019)
The topic of TTIP and CETA was almost completely suppressed in Croatia.1 Those are very important international agreements which could have far-reaching consequences both for the world and individual countries. Maybe Croatia, as well as the EU, is not so much involved in the whole story concerning TTIP. However, CETA is an agreement signed by Canada with the European Union. Therefore, after the approval of the European Parliament, EU provisions, such as the customs policy, can immediately start to apply, which means abolishing duty rates for 99% of the products as early as 1 January 2017. The decision on the CETA conclusion on behalf of Croatia was initiated by the technical Government of Tihomir Orešković at its last session.2 The superficial interpretation of these certainly not harmless agreements is of too little interest to both philosophers and theologians in Croatia, and except for the Centre of Excellence for Integrative Bioethics’3 reaction concerning this question, other philosophical-theological discussions seem to be lacking. The impression is that philosophers and theologians feel these issues do not concern them. In this paper we will try to make clear that the above-mentioned international agreements concern both philosophers and theologians, and that they certainly should, from their field, from the theoretical level, engage in the discussion of the said agreements.
Gotovo je šaptom prošla tema TTIP-a i CETA-e u Hrvatskoj77. Radi se o vrlo važnim međunarodnim sporazumima koji mogu imati dalekosežne posljedice, kako na svijet, tako i na pojedine države. Možda Hrvatska, kao i EU, nije toliko involvirana u cijelu priču kada se radi o TTIP-u. CETA je, međutim, sporazum koji je Kanada potpisala s Europskom unijom, stoga se nakon odobrenja Europskog parlamenta mogu odmah početi primjenjivati odredbe koje su u nadležnosti EU-a, poput carinske politike, a to znači ukidanje carine za 99 % proizvoda već od 1. siječnja 2017. Postupak za sklapanja CETA-e u ime Hrvatske pokrenula je tehnička vlada Tihomira Oreškovića na svojoj posljednjoj sjednici, a za razliku od američko-europskog trgovinskog sporazuma - TTIP-a koji je neslavno propao, CETA je ipak „prošla“. Površno tumačenje ovih nikako bezazlenih sporazuma premalo zanima i filozofe i teologe u Hrvatskoj; osim što se Centar izvrsnosti za integrativnu bioetiku oglasio po ovom pitanju, drugih filozofsko-teoloških rasprava kao da nema. Doima se kako filozofi i teolozi smatraju da se ova pitanja njih ne tiču. U radu ćemo pokušati dati do znanja kako se navedeni međunarodni sporazumi i te kako dotiču i filozofa i teologa, te kako bi se oni iz svog polja na teorijskoj razini svakako trebali uključiti u raspravu o njima.
Bilješke uz tekst.
Bibliografske bilješke uz tekst ; bibliografija: 54 jed.
Summary ; Sažetak.
Keywords: Transatlantic Trade and Investment Partnership -- TTIP -- Comprehensive Economic and Trade Agreement -- CETA; Međunarodni trgovinski sporazumi -- Etičko gledište -- Teološko gledište; Hrvatska